Instrumen Keuangan Sosial Islam Dan Keberlanjutan Lingkungan (SDGs 13) - Abduh, Arridho; Marliyah, Marliyah; Siregar, Saparuddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The issue of climate change has become an urgent global challenge that requires immediate action. Achieving Sustainable Development Goal 13 (SDG 13), which pertains to climate action, has become a top priority in efforts to mitigate the negative impacts that have occurred and are ongoing. In this context, Islamic social finance instruments emerge as a tool with great potential to support environmental sustainability goals. This approach integrates the principles of Islamic social finance, emphasizing justice, sustainability, and fair distribution, with global efforts to address climate change. This article seeks to explain how Islamic social finance instruments can be used as investment vehicles supporting green projects, renewable energy, and other endeavors aimed at reducing carbon emissions and preserving ecosystem balance. We also evaluate the positive impact achieved in attaining SDG 13 through the implementation of these instruments. Despite some hurdles that need to be addressed, such as broader awareness and understanding of Islamic social finance, its potential to contribute to climate change mitigation and the achievement of SDG 13 is significant. This article provides insights into how the Islamic social finance approach can become an integral part of the global solution to address climate change and achieve environmental sustainability.